Food Estate dan Masa Depan Ekonomi Kerakyatan: Antara Strategi Ketahanan Pangan dan Realitas Ketimpangan - Fransiskus Setu; Silvira Angel; Arite L. Yigibalom; Selina Ganul; Elizabeth F. E. Hasiri; Kurnia Martikasari (Universitas Pendidikan Ganesha, 2025)
The Indonesian government initiated the Food Estate programme as a national strategy to strengthen food security through large-scale agricultural production. However, this initiative raised concerns due to limited farmer involvement, environmental degradation, and unequal economic outcomes. This study aimed to examine the extent to which the programme aligns with the principles of a people-centred economy. It employed a qualitative descriptive method based on a systematic literature review of 15 accredited articles published between 2020 and 2025. The data were analysed using the Miles and Huberman model, which includes data reduction, display, and conclusion drawing. The results show that farmer participation remains low and often symbolic. In most project areas, farmers are involved only in technical activities, without meaningful influence in planning or decision-making. The programme also causes serious ecological damage, including deforestation, peatland destruction, and declining water quality. In addition, economic benefits are unequally distributed. Large corporations receive the majority of the profits, while local farmers and cooperatives gain only minimal returns. This study concludes that the Food Estate programme does not fully support inclusive, fair, and sustainable development. Its success cannot be measured solely by production volume. It must also be evaluated based on how well it empowers local farmers, protects the environment, and promotes economic justice in rural communities.